The Relationship Between Parenting Styles and Speech Delay in Children Under 5 Years Old at YARSI Hospital and Its Review in Islam - Naufal Nayaka Rahman (Eduvest - Journal of Universal Studies, 2026)
This study aimed to determine the relationship between child parenting styles and the incidence of speech delay in children under 5 years old at YARSI Hospital. A quantitative analytical cross-sectional design was used with total sampling of 102 children diagnosed with speech delay over 6 months. Parenting styles were assessed for seven caregiver types (father, mother, grandfather, grandmother, uncle, aunt, domestic assistant/ART). Speech delay was classified as functional (environmentally-driven) or non-functional (biologically-linked). For fathers, permissive indulgent parenting was dominant (35.3%). For mothers, authoritarian parenting was dominant (39.2%). Functional speech delay occurred in 72 children (70.6%), while non-functional speech delay occurred in 30 children (29.4%). Bivariate analysis using Chi-Square showed a significant relationship between maternal parenting style and speech delay (p = 0.027). Notably, all non-functional speech delay cases occurred in the authoritarian parenting group, while authoritative parenting had zero non-functional cases. Domestic assistant (ART) parenting also showed a significant relationship with speech delay (p = 0.046). These findings underscore the importance of verbal stimulation in parenting settings, including from domestic assistants, in supporting children's language development. From an Islamic perspective, children are a trust (amanah), and parents bear responsibility for responsive, communicative child-rearing.